2006
DOI: 10.1097/01.mpg.0000221917.80887.9e
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Tumor Necrosis Factor‐alpha A Promoter Gene Polymorphism at Position −308 G→A and Pediatric Inflammatory Bowel Disease

Abstract: Although not necessarily dictating IBD initiation, the TNF-alpha 308 A polymorphism may play a role in modifying the CD phenotype. The polymorphism may influence disease activity as well as more intense inflammatory activity in both forms of IBD and may modify the progression of chronic digestive tract inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 53 publications
2
34
0
Order By: Relevance
“…This is in contrast to the findings of Louis et al [50] who found that the presence of this variant favoured steroid-dependent disease and to a lesser extent fistulizing and colonic disease. Both authors suggested that this genotype indicated a more intense TNF-α-driven inflammatory reaction at the mucosal level.The increased need for surgery in our subjects carrying the variant TNF-α -308 G→A allele is consistent with the observations of other authors, including Cucchiara et al [49] in an Italian pediatric cohort and Sykora et al [42] , in their studies on Czech subjects. The latter group not only genotyped the TNF-α 308 G→A polymorphism, but also measured the serum levels of inflammatory C-reactive protein (CRP), in relation to disease activity.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…This is in contrast to the findings of Louis et al [50] who found that the presence of this variant favoured steroid-dependent disease and to a lesser extent fistulizing and colonic disease. Both authors suggested that this genotype indicated a more intense TNF-α-driven inflammatory reaction at the mucosal level.The increased need for surgery in our subjects carrying the variant TNF-α -308 G→A allele is consistent with the observations of other authors, including Cucchiara et al [49] in an Italian pediatric cohort and Sykora et al [42] , in their studies on Czech subjects. The latter group not only genotyped the TNF-α 308 G→A polymorphism, but also measured the serum levels of inflammatory C-reactive protein (CRP), in relation to disease activity.…”
supporting
confidence: 81%
“…Pooled (random effects) Japanese 235 Kim [30] Korean 263 Vatay [29] Hungarian 212 Gonzalez [35] Spanish 150 Balding [37] Irish 453 Song [38] Han Chinese 248 Fowler [39] Australian 521 Ferreira [40] Portugese 1160 Mittal [41] Indian 186 Sykora [42] Czech 128 Castro-Santos [43] Spanish 489 Yang [32] Korean 687 Celik [33] Turkish 175 Zipperlen Dutch 143 Papo [44] Spanish 167 Sashio [28] Japanese 217 Kim [30] Korean 291 Vatay [29] Hungarian 188 Yamamoto-Furusho [34] Mexican 179 Balding [37] Irish 497 Song [38] Han Chinese 323 Mittal [41] Indian 256 Sykora [42] Jewish 156…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α (-308G/A) polymorphism is reported to be significantly associated with the severity of CD and/or UC in Irish [83], Czech [102], Italian [112], Caucasian patients from New Zealand [128], and Brazilian patients [60]. However, it is not clear whether it is directly involved in pathophysiology of IBD or serve merely as markers in Linkage disequilibrium with susceptibility genes [83].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the carriers of allele A are at greater risk of pancolitis and more likely to require bowel resection in UC and CD [102,112]. The CD patients with allele A were reported to be more resistant to steroids compared with non-carriers.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms in the TNF-α gene and promoter region have been studied extensively on IBD susceptibility and/ or clinical manifestations, although with conflicting findings [15,36].…”
Section: Introductionmentioning
confidence: 99%